2016
DOI: 10.1007/s00784-016-1794-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic factors involved in nocturnal electromyographic activity of masticatory muscles in twins

Abstract: A greater understanding of the contribution of genetic factors could have beneficial uses, including enhanced accuracy of sleep bruxism diagnosis, management of sleep bruxism, and enhanced estimation of the prognosis for patients suffering from sleep bruxism. In addition, it could be also important to adequately evaluate the environmental factors in patients with sleep bruxism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(54 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…18 The same results were also found in Japanese twins. 19 In the studies cited above, with the exception of the last one, the diagnosis of SB used to assess heritability was based on self-report or clinical criteria; the absence of polysomnographic recording to confirm SB using validated research methodology restrains extrapolation of these findings.…”
Section: Significancementioning
confidence: 99%
“…18 The same results were also found in Japanese twins. 19 In the studies cited above, with the exception of the last one, the diagnosis of SB used to assess heritability was based on self-report or clinical criteria; the absence of polysomnographic recording to confirm SB using validated research methodology restrains extrapolation of these findings.…”
Section: Significancementioning
confidence: 99%
“…Detachment of the device during sleep occurred in 13 out of 63 (20.6%) recordings. Detachments have been reported in other studies . Takaoka et al encountered lack of adhesiveness of the EMG device (GrindCare 3.0, Medotech A/S) in one out of 106 (0.9%) participants performing three recordings.…”
Section: Discussionmentioning
confidence: 70%
“…Detachments have been reported in other studies . Takaoka et al encountered lack of adhesiveness of the EMG device (GrindCare 3.0, Medotech A/S) in one out of 106 (0.9%) participants performing three recordings. Shedden Mora et al reported loosened electrodes and failure to charge batteries of the EMG devices (basic PTA device, Haynl Elektronik GmbH with silver‐silver‐chloride electrodes; T3402 Triodes, Thought Technology Ltd) in nine out of 117 (7.7%) participants performing three overnight recordings .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations